Who Is a Right-Wing Supporter? On the Biographical Experiences of Young Right-Wing Voters in Poland and Germany - Mrozowicki, Adam; Trappmann, Vera; Seehaus, Alexandra; Kajta, Justyna (Qualitative Sociology Review, 2019)
This article explores the selected cases of the biographies of right-wing supporters from a larger sample of narrative interviews with young (18-35 years old) people in Poland and Germany. In the existing literature, we can find the socio-economic explanations of the sources of the right-wing turn (related to economic deprivation, precarisation, social exclusion, labor market competition with immigrants and others), as well as cultural explanations connected with new identity politics, symbolic exclusion and divide between society and political elites, the disembedding from previously solid communities, and the fear of new risks related to the inflow of cultural Others. Despite notable exceptions, it is rather uncommon to discuss in this context the actual biographical experiences of right-wing and far-right supporters. In the article, we take a closer look at four biographical cases of people declaring their political support for far right parties. The analysis of the cases leads to the distinction of socio-economic and socio-political pathways to right-wing populist support.